2004
DOI: 10.1128/mcb.24.12.5548-5564.2004
|View full text |Cite
|
Sign up to set email alerts
|

The ETS Transcription Factor ESE-1 Transforms MCF-12A Human Mammary Epithelial Cells via a Novel Cytoplasmic Mechanism

Abstract: Several different transcription factors, including estrogen receptor, progesterone receptor, and ETS family members, have been implicated in human breast cancer, indicating that transcription factor-induced alterations in gene expression underlie mammary cell transformation. ESE-1 is an epithelium-specific ETS transcription factor that contains two distinguishing domains, a serine-and aspartic acid-rich (SAR) domain and an AT hook domain. ESE-1 is abundantly expressed in human breast cancer and trans-activates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
93
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 48 publications
10
93
0
1
Order By: Relevance
“…17,18 Elf3 was shown to be sufficient to transform normal breast epithelial cells 19 and markedly increase their survival. 20 Overexpression of Pdef has been found to stimulate cell mobility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Elf3 was shown to be sufficient to transform normal breast epithelial cells 19 and markedly increase their survival. 20 Overexpression of Pdef has been found to stimulate cell mobility and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, overexpression of another family member, PEA3, induces branching morphogenesis in TAC-2 MECs, revealing a level of phenotypic specificity that suggests each factor may promote the transcription of a distinct set of target genes (52). Furthermore, according to a recent study, the transforming effects of ESE-1 involve a novel cytoplasmic function independent of its transcriptional activity, suggesting an additional level of complexity to the activities of Ets family proteins (53).…”
Section: Transcription Factorsmentioning
confidence: 99%
“…19 However, transient nuclear ESE-1 expression in MCF-10A/MCF-12A benign, non-transformed mammary epithelial cells results in apoptosis 19 and/or decreased cell proliferation, 50 whereas similar nuclear ESE-1 expression in fully transformed mammary epithelial cells fails to induce apoptosis. 19 Although it was previously presumed that many ETS factors transform mammary epithelial cells via their nuclear transcriptional functions, it has been shown that ESE-1 protein is localized within the cytoplasm in human breast cancer cells and that initiation of transformation of benign MCF-12A cells by stable expression of ESE-1 is mediated by the SAR domain of ESE-1, which acts in the cytoplasm via an unknown nonnuclear and non-transcriptional mechanism. 19 Importantly, the nuclear localization of ESE-1 protein maintains the transformed phenotype of fully transformed mammary epithelial cells.…”
Section: Ese-1 In Mammary Gland Development and Breast Cancermentioning
confidence: 99%
“…19 Although it was previously presumed that many ETS factors transform mammary epithelial cells via their nuclear transcriptional functions, it has been shown that ESE-1 protein is localized within the cytoplasm in human breast cancer cells and that initiation of transformation of benign MCF-12A cells by stable expression of ESE-1 is mediated by the SAR domain of ESE-1, which acts in the cytoplasm via an unknown nonnuclear and non-transcriptional mechanism. 19 Importantly, the nuclear localization of ESE-1 protein maintains the transformed phenotype of fully transformed mammary epithelial cells. 51 Others have reported that the signaling kinase, Pak1, interacts with and selectively phosphorylates ESE-1 at serine 207, which is located within the SAR domain.…”
Section: Ese-1 In Mammary Gland Development and Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation